The Influence Of Trust In Mediating E-Wom And Social Media Usage Toward Purchase Decision Involvement At Tiktok - Putri, Olimvia Agustina; Octavia, Damayanti (eProceedings of Management, 2025)
Since digital technology has advanced so quickly, consumer behavior has changed, and social media platforms have become powerful marketing tools. Specifically, TikTok has become well-known for combining entertainment and e-commerce, allowing viewers to discover products in real time and make purchases through TikTok Shop.This study examines the influence of electronic word of mouth (e-WOM) and social media usage on purchase decision involvement, with trust as a mediating variable. Drawing on existing literature, the study highlights how features such as reviews, live streaming, and influencer endorsements significantly impact consumer trust and engagement. However, the abundance of information on social media raises concerns regarding credibility, making trust a vital factor in processing online content and making purchase decisions. The findings aim to provide insights into the interplay between e-WOM, social media usage, and trust in shaping consumer involvement in purchase decisions on TikTok. This study fills a research gap by exploring the mediating role of trust in a rapidly evolving social commerce environment. Keywords: Social Media Usage; Electronic word of mouth; Purchase decision; Trust.